C21orf91 Regulates Oligodendroglial Precursor Cell Fate—A Switch in the Glial Lineage? - Reiche, Laura; Göttle, Peter; Lane, Lydie; Duek, Paula; Park, Mina; Azim, Kasum; Schütte, Jana; Manousi, Anastasia; Schira-Heinen, Jessica; Küry, Patrick (Frontiers in Cellular Neuroscience, 2021)
Neuropathological diseases of the central nervous system (CNS) are frequently associated with impaired differentiation of the oligodendroglial cell lineage and subsequent alterations in white matter structure and dynamics. Down syndrome (DS), or trisomy 21, is the most common genetic cause for cognitive impairments and intellectual disability (ID) and is associated with a reduction in the number of neurons and oligodendrocytes, as well as with hypomyelination and astrogliosis. Recent studies mainly focused on neuronal development in DS and underestimated the role of glial cells as pathogenic players. This also relates to C21ORF91, a protein considered a key modulator of aberrant CNS development in DS. We investigated the role of C21orf91 ortholog in terms of oligodendrogenesis and myelination using database information as well as by means of cultured primary oligodendroglial precursor cells (OPCs). Upon modulation of C21orf91 gene expression, we found this factor to be important for accurate oligodendroglial differentiation, influencing their capacity to mature and to myelinate axons. Interestingly, C21orf91 overexpression initiates a cell population coexpressing astroglial- and oligodendroglial markers indicating that elevated C21orf91expression levels induce a gliogenic shift towards the astrocytic lineage reflecting non-equilibrated glial cell populations in DS brains.